Eﬀectiveness of high-intensity laser therapy in the treatment of shoulder impingement syndrome: a systematic review and meta-analysis of randomised clinical trials - de la Barra Ortiz, Hernán Andrés; Cortés, Antonia; Pizarro, Fernando; Sabaj, Nicolás; Sainz, Esteban (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. High-intensity laser therapy (HILT) is a recent resource promoted as an alternative to relieve pain and improve function in patients with subacromial impingement syndrome (SAIS). The aim of this review was to assess the eﬀects of HILT on pain in patients with SAIS.Methods. Electronic databases, including PubMed, Web of Science, Scopus, CINAHL, Science Direct, Cochrane Library, the PEDro database, and Google Scholar (updated to January 8, 2025), were searched for clinical trials comparing HILT with other physical therapy treatments in patients with SAIS. The main outcomes evaluated were pain intensity, range of motion (ROM), and disability for diﬀerent scales and instruments. The results of VAS, range of motion, CMS, and SPADI were analysed, evaluating the quality of RCTs with the Cochrane risk of bias (RoB) 2.0 tool and the evidence with the GRADE approach.Results. Nineteen studies were included, generally presenting a low RoB, except for outcome data measurement and bias due to deviations from the intended intervention. RCTs reported a reduction in pain and an improvement in functionality in the meta-analysis. VAS MD = –1.56 cm (95% CI: –2.1,1.0); CMS MD = 4.0% (95% CI: 1.7, 6.2). Furthermore, there were signiﬁcant improvements in ﬂexion and abduction favouring HILT: ﬂexion MD = 12.8° (95% CI: 2.5, 23.1);abduction MD = 15.3° (95% CI: 4.4,26.1). Only changes in pain and ROM were both statistically signiﬁcant (p < 0.05) and clinically signiﬁcant.Conclusions. This SR supports the eﬀects of HILT on pain, ROM, and disability. It agrees with previous reviews on LLLT, validat-ing both treatment options. Although the evidence was assessed as important, methodological inconsistencies are noted in some RCTs that could aﬀect the certainty.
Keywords: systematic review; phototherapy; shoulder impingement syndrome; laser therapy; shoulder pain; high-intensity laser therapy